(untitled) (Global Journal of Science Frontier Research, 2016)
The simultaneous analyses of NMP and DMAc in synthetic fibers that have been regulated recently due to their human hazard properties were studied by both a conventional GC-MS method and a thermal desorption(TD)-GC-MS method that uses Py-GC-MS instrument using the thermal desorption function. Method validation characteristics such as linearity, precision of peak area and retention time, limit of quantification on their determination using a new TD-GC-MS method were found to be acceptable according to the well-recognized method validation guidelines and the current regulation limit. Recovery ratios of DMAc from the spiked synthetic fibers were estimated to be 95.2% to 97.1% with Soxhlet extraction using methanol as measured by GC-MS. Residual amounts of NMP and DMAc in commercial meta-aramid, polyester, and spandex fibers were measured by and GC-MS and TD-GC-MS, respectively and showed a good correlation between two methods with the ratio of 85.5% to 119%. Results of this study suggested that the TD-GC-MS analysis can provide both a good screening and a quick determination of NMP and DMAc in synthetic fibers without any solvent extraction of fiber samples that is a routine and time consuming pretreatment in the conventional GC-MS analysis.